Sedimented professional identities: early childhood education pre-service teachers. Issue 3 (18th May 2020) - Keary, Anne; Babaeff, Robyn; Clarke, Sharryn; Garnier, Kathryn
ABSTRACT: A shifting notion in the field of early childhood education (ECE) is what it is to be a 'professional'. This paper examines third-year early childhood undergraduate pre-service teachers (PSTs) developing understandings of notions of 'professionalism' as expressed through identity texts. PSTs develop knowledge of standards, frameworks and policies that impact on their professional work and undertake a review of legislative requirements. As a counterpart, the intent of this teaching unit and its associated research was to move PSTs beyond regulatory requirements to assist them to develop a critical awareness of the notion of 'professionalism'. To gather evidence of PSTs own dynamic perceptions of what 'professionalism' entails, insights were gleaned from the ways they responded to an identity text workshop activity that asked them to represent 'professionalism' through visual imagery and text. These insights are discussed in terms of 'sedimented identities' and three sites of meaning of an image. The findings suggest that developing conceptions of professionalism in ECE are sedimented over time through engagement with generic principles from the workplace and official government documents that regulate the profession of early childhood education.